Peningkatan Pembelajaran Melalui Situs Media Online dengan Metode Blended Learning Pada Masyarakat Desa Bojongcae - Indri Arrafi Juliannisa (Universitas Islam Nahdlatul Ulama Jepara, 2020)
This community service activity is intended to provide more knowledge to the residents of Bojongcae- Lebak Regency, especially for parents, and children and teenagers who relied on manual and limited teaching material for education with increasing the ability of partner groups in the world of education. The partner groups in this study are housewives who are members of the PKK group, and teenagers who have the ability to speak English better than housewives and other teenagers.The material provided in this community service program is internet based using social media instragram with the account name